Analisis Faktor Determinan Perilaku Agresif Taruna di Politeknik Pelayaran Banten - Dwi Endah Kurniasari; Pramudyasari Nur Bintari; Weli Agus Setiawan (Intitut Agama Islam Nasional Laa Roiba Bogor, 2025)
This study aims to identify and analyze the determinants influencing aggressive behavior among cadets at the Banten Maritime Polytechnic. Maritime education, with its semi-military nature, demands high discipline and mental preparedness, but in practice often creates psychological stress that can impact student behavior. Using a qualitative approach through a case study method, data was collected through direct observation, semi-structured interviews, and an Analytical Hierarchy Process (AHP)-based survey. The results indicate five main factors influencing aggressive behavior among cadets: stress, self-concept, emotional management, family background, and the dormitory environment. Of these five factors, stress is the most dominant factor. This study concludes that aggressive behavior is not solely caused by individual factors but also reflects social dynamics and an education system that is not fully responsive to the psychological needs of cadets. Comprehensive interventions are needed, including counseling services, stress and emotion management training, and improvements to the social environment on campus and in the dormitory to create a healthier and more supportive educational atmosphere.